Progress and Effectiveness of the Health Status and Equity of Health Service Utilization of Rural Residents in Ningxia During 10 Years after the New Healthcare Reform - QIAO Hui, XIE Yongxin, XIAO Wenwen, GAO Baokai, CHEN Kexin (Zhongguo quanke yixue, 2023)
Background The health care and health system reform is a worldwide issue. In 2009, China launched a new round of health care and health system reform. Over the past ten years, especially since the 18th National Congress of the Communist Party of China, the reform has brought tangible benefits to nearly 1.4 billion people. The decade of the new medical reform, which concentrates the interests of all parties, is a highlight of China's medical and health services. The discussion and demonstration of the reform effectiveness has become a hot topic in the academic field. Objective To sort out and analyze the data changes of the health status and equity of health service utilization of rural residents in Ningxia during the process of new medical reform and the reflected development effectiveness. Methods The baseline data was collected from the "Family Health Interview Survey for Rural Residents" in Ningxia in 2009, and the follow-up data in 2015 and 2019. The self-rated unhealthy rate and prevalence of chronic diseases were selected as indicators to measure the health status of residents, and the two-week consultation rate and hospitalization rate were selected as indicators to measure the health service utilization of residents. The concentration index (CI) and its decomposition method were used explore the health status and equity of health service utilization of rural residents in Ningxia in the past decade of the new medical reform. Results During the decade of the new medical reform, the self-rated unhealthy rate of rural residents in Ningxia decreased, and the prevalence of chronic diseases increased year by year. The self-rated unhealthy rate in 2009, 2015 and 2019 was 20.37% (4 107/20 160), 17.75% (3 216/18 114) and 19.51% (3 527/18 074) ; the prevalence of chronic diseases was 13.01% (2 623/20 160), 19.45% (3 523/18 114) and 26.28% (4 750/18 074), respectively. The overall changes in health service utilization showed an upward trend, the two-week consultation rate in 2009, 2015 and 2019 was 6.43% (1 296/20 160), 5.66% (1 026/18 114) and 8.06% (1 457/18 074) ; the hospitalization rate was 8.89% (1 792/20 160), 10.66% (1 931/18 114) and 13.23% (2 392/18 074), respectively. Equity of health and health service utilization have been improved, the CI of the self-rated unhealthy rate of rural residents in Ningxia in 2009, 2015 and 2019 was -0.024 1, -0.095 2 and -0.098 0; the CI of the prevalence of chronic diseases in 2009, 2015 and 2019 was -0.001 3, -0.081 5 and -0.081 0, respectively; the CI of two-week consultation rate was 0.068 8, -0.011 3, -0.051 2, and the CI of two-week hospitalization rate was 0.039 0, -0.029 4, -0.061 2, respectively. The main influencing factors of equity gradually evolved from the relatively single phenomenon of economic income being the dominant factor to the situation where age, economic income, chronic diseases, education level and other factors interact in multiple ways. Conclusion The health status and equity of health service utilization of rural residents in Ningxia has been improved in the past decade of the new medical reform. However, more attention should be paid to new issues and inequities caused by the aging population and changes in social structure.